First Sternal Cleft Repair Using a Porous Alumina Ceramic Prosthesis in a 9-Year-Old Child - Fouilloux, Virginie; Bertin, François; Peltier, Emilie; Jouve, Jean-Luc (European Journal of Pediatric Surgery Reports, 2019)
Sternal cleft is a rare congenital abnormality, often associated with other congenital defects. We present the case of a 9-year-old child with complete sternal cleft, treated with an innovative sternal prosthesis. Surgery was performed to protect the heart and also, as pulsations was visible, leading to serious esthetical concerns, to enhance school integration, which was difficult. The porous alumina device used was initially designed for sternal reconstruction after refractory deep sternal wound infection or carcinoma. Surgery and early follow-up were simple. There was no complication and the follow-up of more than 1 year reveals a good healing without breath discomfort and a correct development of the chest wall. In this rare indication, the alumina ceramic sternal prosthesis offers a reliable alternative to classical methods, such as muscle flap, autogenous tissue transfer, costal homograft, and other prosthetic materials like mesh or synthetic patch.
Keywords: sternal cleft; prosthesis; bioceramics; tissue engineering